The therapeutic prospects of N-acetylgalactosamine-siRNA conjugates - Zhang, Lei; Liang, Yayu; Liang, Guohui; Tian, Zhili; Zhang, Yue; Liu, Zhihui; Ji, Xinying (Frontiers in Pharmacology, 2022)
RNA interference has become increasingly used for genetic therapy following the rapid development of oligonucleotide drugs. Significant progress has been made in its delivery system and implementation in the treatment of target organs. After a brief introduction of RNA interference technology and siRNA, the efficiency and stability of GalNAc-siRNA conjugates are highlighted since several oligonucleotide drugs of GalNAc have been approved for clinical use in recent years. The structure and features of GalNAc-siRNA conjugates are studied and the clinical efficiency and limitations of oligonucleotide-based drugs are summarized and investigated. Furthermore, another delivery system, lipid nanoparticles, that confer many advantages, is concluded, includ-ing stability and mass production, compared with GalNAc-siRNA conjugates. Importantly, developing new approaches for the use of oligonucleotide drugs brings hope to genetic therapy.